2021
DOI: 10.1177/13634593211017187
|View full text |Cite
|
Sign up to set email alerts
|

“It’s not all nice and fun”: Narrating contested illness on YouTube and Instagram

Abstract: This empirical study draws on insights from narrative theory to tease out how women with a contested illness narrate their experiences on social media. Based on 13 months of online observations between 2017 and 2019, I analyse how a sample of eight highly active Dutch female social media users share their illness on YouTube and Instagram. In addition, I interviewed five of them. Through their online performances, the women in this study illustrate their investment in self-care practices, whilst simultaneously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…These findings are also congruent with other studies on contested conditions which demonstrate the patients' vulnerability in front of the symptoms, despite their efforts to overcome the challenges (e.g. Groenevelt, 2021). In particular, although the students often adopt a rather active approach to their illness management, demonstrating their active engagement in self-diagnosis and decision-making processes, or their struggle to overcome barriers, they often construct passive identities in relation to their conditions, with symptoms constructed as if coming from the outside, and affecting their lives directly (cf.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…These findings are also congruent with other studies on contested conditions which demonstrate the patients' vulnerability in front of the symptoms, despite their efforts to overcome the challenges (e.g. Groenevelt, 2021). In particular, although the students often adopt a rather active approach to their illness management, demonstrating their active engagement in self-diagnosis and decision-making processes, or their struggle to overcome barriers, they often construct passive identities in relation to their conditions, with symptoms constructed as if coming from the outside, and affecting their lives directly (cf.…”
Section: Discussionsupporting
confidence: 90%
“…In particular, although the students often adopt a rather active approach to their illness management, demonstrating their active engagement in self-diagnosis and decision-making processes, or their struggle to overcome barriers, they often construct passive identities in relation to their conditions, with symptoms constructed as if coming from the outside, and affecting their lives directly (cf. Groenevelt, 2021;Paxman, 2021;Sowińska, 2018Sowińska, , 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Together with the sense of 'relentless responsibility' that comes with caring for their Instagram feed and managing online relationships, the mothers interviewed for this study felt additional pressure to align their Instagram engagement with social media norms of (self-)presentation, including positivity as a marker of adherence to 'proper' caregiving (Groenevelt 2021). Concessions from the women in this study that they sometimes want to give up on their Instagram and even on their care, further demonstrate the gravity of the bind they find themselves in.…”
Section: The Burdens Of Instagrammentioning
confidence: 99%
“…However, since pain is a phenomenon that is hard to communicate ( Scarry 1988 ), it is not easy to create pain narratives. Recent studies have shown that more flexible, intermodal and interactive types of narrating, as afforded by the internet and social media, might facilitate pain storytelling ( Gonzalez-Polledo and Tarr 2016 ; Groenevelt 2021 ; Ressler et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%